Book review:΄ Greg, PETERS, Peter of Damascus. Byzantine Monk and Spiritual Theologian (Toronto: Pontifical Institute of Mediaeval Studies, Studies and Texts 175, 2011) - SAHAS, Daniel (Byzantina Symmeikta, 2013)
Βιβλιοκρισία: Greg, PETERS, Peter of Damascus. Byzantine Monk and Spiritual Theologian (Toronto: Pontifical Institute of Mediaeval Studies, Studies and Texts 175, 2011), 182 p. + Appendices and Bibliography.